Problem of Harmonization of Legal Norms with the Needs of Police Investigations by Using High-Tech Instruments for Searching Information (Law and Safety, 2021)
The problem of harmonization of legal norms with the needs of police investigations with the use of high-tech data search tools has been analyzed. It has been determined that the transition of police structures from a reactive to a proactive paradigm is unalterable in the modern high-tech turbulent world. The problem’s structuring has been accomplished. It has been determined that the ways of its solution lie both in the legal plane and in the technical one, where the legal aspect of the problem has two components – international and national. The experience of world practice in the field of the researched problem has been analyzed. The authors have accomplished the analysis of international legal norms in the field of personal data protection, as well as the analysis of the most typical national regulations – starting from the approach of solving the problem in democracies, which for centuries strictly adhere to the doctrine of privacy and private property, to the most radical approach in China. The ways of its solution have been outlined. Technical mechanisms of the solution have been suggested. It has been determined that the settlement of any of the aspects does not mean the solution of the problem in the whole. The matter of its fundamental solution lies in the legal plane, and since organized crime in the context of global digitalization of the world community is becoming increasingly transnational in nature, it is primarily a field of international law. It has been determined that the complete solution of the problem has a complex character and should contain a number of normative and legal acts at the level of international and national law, as well as certain technical measures that ensure the legality of personal data collection procedures used by police in the most modern high-tech, tool-making, analytical systems.
Keywords: globalization; high technologies; proactive policing; information and analytical systems; “poor signals”